Effects of Metformin Therapy on Anti-Mullerian Hormone (AMH) Levels in Polycystic Ovary Syndrome Patients with Insulin Resistance at Palembang - Fatimah Usman; Rizani Amran; Heriyadi Manan; Zulkarnain Zulkarnain (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Anti-Mullerian Hormone is useful in examining folliculogenesis and ovarian abilities. Previous research found that follicular fluid and serum in PCOS women containing high AMH levels. As therapy in PCOS with insulin resistance, metformin, an insulin sensitizer agent can be given. The efficacy of metformin therapy in inducing ovulation is more due to the local action of metformin on the ovaries rather than the systemic improvements that result both metabolically and hormonally. We conducted this study to evaluate the levels of Anti-Mullerian Hormone (AMH) in women with polycystic ovarian syndrome (PCOS) with insulin resistance before and after metformin therapy. An analytic observational study with cross-sectional design. Seventy PCOS women with insulin resistance, taking metformin for 3 months, were enrolled in this study. Serum levels of AMH was assessed before and after treatment, and the difference between them was analyzed with student t-test. Diagnosis of PCOS is made based on Rotterdam criteria and insulin resistance by HOMA-IR calculation. This study was conducted at the Fertility and Reproductive Endocrinology Polyclinic of Dr. Mohammad Hoesin Palembang hospital and Imaya clinic. The mean age of PCOS patients with insulin resistance ranges from 25-30 years, with a mean age of 28.61±3.883. The mean AMH levels prior metformin therapy was 7.6957±0.6001 ng/ml; mean AMH after therapy was 7.5914±0.57678 ng/ml; and there are significant differences (p <0.001). The mean AMH levels in all patients were 0.10429. Based on body mass index (BMI), a total of 52 respondents (74.29%) met the criteria for obesity and 18 respondents (25.71%) nonobese. There is a relationship between AMH levels and the number of follicles (p <0.01), with an OR of 1.5. AMH levels decreased significantly after metformin therapy in PCOS patients with insulin resistance.